Assessing Benefit-Incidence Results Using Decompositions: The Case of Health Policy in Argentina - Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This paper discusses the use of aggregate and microeconometric decompositions to compare benefit-incidence results over time and across regions. Decompositions are applied to explore changes in targeting in health policies directed to pregnant women and children under 4 in Argentina. The results suggest that although health public programs are pro-poor, incidence changes in the last 5 years have been pro-rich due to two different factors: a substantial reduction in the fertility rate of poor couples, and an increase in the use of public facilities by wealthier households, likely triggered by the economic crisis that Argentina has suffered since 1998.
Keywords: J2; J6; D3; O54; 330; protección; informalidad; empleo; América Latina.